The Role of Corporate Governance Perception Index Score in Increasing Stock Prices - Anas Anas; Sri Hartono (Return : Study of Management, Economic and Bussines, 2024)
This study analyzes the role of Corporate Governance, specifically using the Corporate Governance Perception Index Score (CGPI), in moderating the influence of Revenue, Net Profit Margin, and Return on Equity on stock prices of companies ranked in the Corporate Governance implementation ranking conducted by the Indonesian Institute for Corporate Governance (IICG). This study uses quantitative research, the population for this study includes all companies that participated in the CGPI ranking from 2014 to 2022, with the criterion of having ranking data for at least five consecutive years, resulting in data from nine companies. The statistical analysis employed descriptive analysis and Moderated Regression Analysis using E-views software, as the data type is panel data, which combines cross-sectional and time-series data. The analysis indicated that among the three independent variables examined, only Return on Equity had a positive effect on stock prices. In contrast, Revenue and Net Profit Margin did not significantly affect stock prices and tended to signal negative implications. After including Corporate Governance as a moderating variable, the results indicated that Corporate Governance could only slightly strengthen the influence of Revenue on stock prices. However, it was not effective in enhancing the influence of Net Profit Margin or Return on Equity on stock prices.